Physics and Biology : From Molecules to Life - Allemand, Jean Francois and Desbiolles, Pierre; World Scientific (Firm) (Singapore ; World Scientific Pub. Co., 2014)
Do you often lose your keys? You will find in this book the best strategy to find them, or at least the one deduced from statistical physics. What is the link with biology? Some proteins use the same strategy to find their target inside a living cell. This example illustrates one of the many links between physics and biology. These links result from an intense research activity in the past years at the interface between those two disciplines. This book describes some of the most recent progresses at this interface: from instrumental progresses used in biology to the mechanical description of a cell, to molecular motors, from brain activity mechanisms to auditory or sensory perception. Many fields are covered from the molecular to the scale at the organ level. A few biological notions are presented in the first chapter that may help to access the biological aspects of the others. In the end this book may interest people passionate in science, from the simple amateur to the advanced researcher level.
1. Some biology basic principles. 1. Introduction. 2. At the cellular level. 3. At the molecular scale -- 2. Fluorescence microscopy for biological imaging. 1. Introduction. 2. Fluorescence. 3. Fluorescence microscopy. 4. Single molecule imaging. 5. Conclusion and perspectives -- 3. Mechanical studies on single molecules: general considerations. 1. Elements of molecular biology. 2. Advantages and drawbacks of single molecule studies. 3. Order of magnitude of the relevant parameters at the single molecule level. 4. Single molecule manipulation techniques. 5. Comparison of the different techniques. 6. DNA mechanical properties. 7. Conclusion -- 4. Molecular motors. 1. A rotating motor: ATP synthase. 2. Myosins: a linear motor example. 3. A motor on DNA: the example of the RNA polymerase. 4. Conclusion -- 5. Cellular mechanics and motility. 1. Mechanical properties of eukaryotic cells. 2. Cell movement or cell motility. 3. Simplified systems for a controlled study. 4. Conclusion and perspectives -- 6. Exploring neuronal activity with photons. 1. Introduction. 2. Information coding. 3. Optical recordings of neuronal activity. 4. Functional organization of the cortex at the level of a cortical column. 5. Microarchitecture of a cortical column. 6. Dynamics of neuronal populations. 7. Outlook -- 7. Physical principles of hearing. 1. Psychophysical properties of hearing. 2. The cochlear amplifier. 3. Mechanosensory hair cells. 4. The "critical" oscillator as a general principle of auditory detection -- 8. Sensing through friction: the biomechanics of texture perception in rodents and primates. 1. Cutaneous mechanoreceptors of the human glabrous skin. 2. The neural basis of roughness perception. 3. Mechanical filtering of tactile information by the skin tissue. 4. Whisker perception in rodents. 5. The whisker as a transduction line. 6. Conclusion -- 9. Intermittent search strategies. 1. Introduction. 2. Animals looking for food. 3. Model of intermittent search. 4. Minimizing the search time. 5. Should animals really perform Levy strategies? 6. How does a protein find its target sequence on DNA? 7. Active intermittent transport incells. 8. Optimizing the kinetic rate constant. 9. Robustness of the results. 10. Conclusion.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Biophysics; Electronic books